Applying maslow’s motivation theory to enhance teacher productivity in islamic boarding schools - Setyaningrum, Ari Eka; Rahmania, Fatmaya Anisa (Asian Journal Collaboration of Social Environmental and Education, 2025)
Background: Education is a fundamental pillar in developing high-quality human resources, with teachers playing a central role. Teacher productivity is strongly influenced by work motivation, which is closely linked to the fulfillment of needs based on Maslow’s hierarchy. This study aims to analyze the application of Maslow’s theory in improving teacher productivity, a pesantren-based school with an integrative curriculum. The focus is to identify dominant teacher needs and propose strategic recommendations to enhance motivation and productivity. Method: This qualitative descriptive study used structured and unstructured interviews with 14 teachers, participatory observation, and school document analysis. Data were thematically analyzed based on Maslow’s hierarchy; physiological, safety, social, esteem, and self-actualization needs. Findings: The study identified seven dominant teacher needs; (1) salary increase, (2) regular recognition, (3) modern learning facilities, (4) improved work infrastructure, (5) regular training, (6) enhanced school safety, and (7) healthcare access. Most teachers reported that physiological (salary) and esteem needs were not optimally fulfilled, while self-actualization (professional development opportunities) was relatively well-supported. Teachers generally responded positively to the work environment, although dissatisfaction in welfare and recognition affected motivation. Conclusion: Fulfilling Maslow’s hierarchy of needs is crucial for enhancing teacher productivity. Strategic recommendations include optimizing budgets for welfare, implementing performance-based rewards, improving support facilities, and ensuring continuous training. Schools should integrate responsive policies to foster a motivational work environment. Novelty/Originality of this article: This study offers practical insights for Islamic boarding schools implementing the independent curriculum. The analysis of teacher needs through Maslow’s framework within this unique setting provides a holistic policy recommendation, combining welfare, professional growth, and a culture of appreciation which is contributing to underexplored literature on teacher motivation in Islamic education institutions.